A comprehensive study of the short-circuit ruggedness of silicon carbide power MOSFETs - Romano, Gianpaolo; Fayyaz, Asad; Riccio, Michele; Maresca, Luca; Breglio, Giovanni; Castellazzi, Alberto; Irace, Andrea (IEEE, 2016)
The behavior of Silicon Carbide Power MOSFETs under stressful short circuit conditions is investigated in this paper. Illustration of two different short-circuit failure phenomena for Silicon Carbide Power MOSFETs are thoroughly reported. Experimental evidences and TCAD electro-thermal simulations are exploited to describe and discriminate the failure sources. Physical causes are finally investigated and explained by means of properly calibrated numerical investigations, and are reported along with their effects on devices short-circuit capability.